Can the acceptance of a carbon tax be increased? The effect of tax revenue recycling and redistribution among households and companies - Anders Dugstad; Kristine M. Grimsrud; Henrik Lindhjem (Statistics Norway, Research Department, 2023)
Effective carbon taxation is essential to achieving the green transition. However, there is typically stiff opposition to carbon taxation due to perceived or actual adverse equity and other impacts. Hence, a better understanding of which factors, including the use of tax revenue, can increase acceptability is essential. To date, stated preference methods have rarely been used to analyse this issue and, when used, have focused only on households' acceptance. We conduct two identical national choice experiment surveys of Norwegian households and companies, respectively, including carbon tax levels and associated emission reductions and different revenue recycling options as attributes. We find that acceptance for higher tax levels increases among both groups if revenue finances climate mitigation measures. There is some heterogeneity among the groups with regard to using revenue to reduce different dimensions of inequality. Simulating policy options, we find acceptance for the highest carbon tax among both groups when revenue is used both to finance climate mitigation measures and to reduce rural-urban inequalities. This policy option points to an acceptable carbon tax close to an estimated level necessary for reaching the most ambitious climate target set by the Norwegian government. An effective carbon tax level can potentially be achieved in Norway with modest efficiency costs to alleviate inequality.
Keywords: H23; Q48; Q58; R48; 330; Climate change; Carbon tax; Policy acceptance; Willingness to pay; Earmarking; Tax revenue